Inventarisasi Tanaman Berpotensi Sebagai Indikator Asam-Basa Alami Di Kota Kupang - Mahmud, Nur R. Adawiyah; Ihwan, Ihwan; Jannah, Nur (bionature, 2018)
Abstract. Â This study investigated a natural acid-base indicator which is extracted from plants in Kupang city. There are 14 plants that potential as a source of natural indicator for acid base titration, i.e, Kol Ungu (Brassica oleracea Capitata Group), Turi Merah flower (Sesbania grandiflora L. Pers), Belimbing Wuluh flower (Averhoa bilimbi L), Kaktus Merah fruit (Opuntia vulgaris Mill), Ruelia flower (Ruellia simplex), Flamboyan flower (Delonix regia), bugenvil flower (Bougainvillea spectabilis Willd.), Bayam Merah leaves (Amaranthus tricolor L.) Jamblang fruit (Syzygium cumini L.), Murbey fruit (Morus alba L.), Pinang fruit (Areca catechu L.), Sirih fruit (Piper betle L.), Kunyit (Curcuma longa Linn), and Nanas Kerang leaves (Rhoeo discolor). Plants extract shows a sharp color change in acid and base solution. Promising results as a natural indicator also shown in acid base titration which is have similar equivalent point to synthetic indicator. We can use these natural indicators as an alternative to synthetic indicator because they are found to be simple, very useful, cheap, easy to extract, accurate, and eco-friendly. Keywords: Plant, Natural indicator, Acid-Base